EVALUASI METODE KERJA PEKERJAAN PEMASANGAN KERAMIK DENGAN MENGGUNAKAN METODE TIME AND MOTION STUDY (STUDI KASUS TUKANG BATU PADA PEKERJAAN PEMASANGAN KERAMIK DI WILAYAH BANYUMAS DAN SEKITARNYA) - Dwi Sri Wiyanti (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2011)
Abstrack To deal with the competition among the construction entrepreneurs and stay exist in construction business improvements are needed. One improvement that can be done is in the ability to increase the productivity of labor that work on the construction projects. Increasing labor productivity that work on a construction project can be done through improvement of work methods used by those workers.One of work methods improvement that can be done is  by evaluating the working methods of a job in construction projects. In the present study the job is the work of ceramics tile installation.This study used Nonparticipant observation data collection technique and Time and Motion Study methods. After recording the activities of  masons when installing tiles with a video camera, the recording are observed so that we know the variety of methods that to used by the mason and the required time to complete activities based on a variety of working methods. Then do the calculation of productivity and observe the effects of work methods on productivity.After analyzing process  it is expected that we can discover various methods of work and its  productivity so that we know which one is the most effective method that generates high productivity. Working methods that generate the highest productivity is expected to be applied to improve the productivity of masons at ceramic works.Keyword : Working Methods, Ceramics installation, Time and Motion Study, Banyumas